2017
DOI: 10.1016/j.pjnns.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Transdural herniated lumbar disc disease with muscle patch for closure of durotomy – A Brief review of literature

Abstract: Autologous muscle patch with fibrin glue for dural rent closure is a simple and effective method which can be performed by endoscopic or minimally invasive approaches. Suturing the dura, being a tedious and cumbersome procedure can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Thohar Arifin et al suggested a microsurgical approach with a median or paramedian dural incision to better observe the intradural disc and avoid damage to the nerve roots (31). Huliyappa et al found that after the removal of the intervertebral disc in the spinal canal, further resection of the intervertebral disc was not required, and intervertebral fusion might not be required (32). In our case, we perform the standard laminectomy followed by microscopically assisted incision of the dural sac to separate the nerve roots and remove the disc fragments.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thohar Arifin et al suggested a microsurgical approach with a median or paramedian dural incision to better observe the intradural disc and avoid damage to the nerve roots (31). Huliyappa et al found that after the removal of the intervertebral disc in the spinal canal, further resection of the intervertebral disc was not required, and intervertebral fusion might not be required (32). In our case, we perform the standard laminectomy followed by microscopically assisted incision of the dural sac to separate the nerve roots and remove the disc fragments.…”
Section: Treatmentmentioning
confidence: 99%
“…In 2018, Kim et al reported the first case of lumbar 2/3 ILDH via transforaminal endoscopic approach, and a good clinical effect was obtained after an 8-month follow-up (13). In 2017, Huliyappa et al reported a case of lumbar 5/sacral 1 segment ILDH treated with posterior percutaneous spinal endoscopy (32). In 2020, Moon et al reported a case in which the lumbar 2/3 intervertebral disc was removed under a laparoscope (33).…”
Section: Treatmentmentioning
confidence: 99%
“…Lumbar IDH is a rare classification of disc herniation [ 11 , 12 ]. In addition, IDH is difficult to diagnose preoperatively based on clinical symptoms or radiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of IDH remains unclear, however few theories have been proposed. Several reports suggested that certain factors like reduced epidural space resulting from congenital or iatrogenic narrowing of spinal canal, adhesions between annulus fibrosus, posterior longitudinal ligament (PLL) and ventral dura matter were responsible for IDH [7], [8]. Among the aformentiond pathogenesis adhesion between PLL and ventral dura matter was considered to be an important factor [9], [10].…”
Section: Discussionmentioning
confidence: 99%